E-Logistics: A Bibliometric and Visualization Analysis. Issue 4 (2nd October 2022) - Burak, Mehmet Fatih
ABSTRACT: This study was carried out to perform bibliometric analysis on e-logistics, which could not be found to be examined before in the literature, and create bibliometric networks through visualizations. The VOSviewer (ver. 1.6.17) program was used in the creation and visualization of bibliometric networks. According to the analysis results of this study, most publications in the field of e-logistics were published in 2004, the languages of the publications were mostly English, the country with the most publications was China, the most cited authors were Feng-Cheng Tung, Su-Chao Chang, and Chi-Min Chou, 2008 and according to Web of Science (WoS) categories, the most publications were understood to be in the computer science information systems category. According to the results of the bibliometric analysis using the creation and visualization of bibliometric networks, the most cited author was Ulieru, M. based on the co-citation author analysis, the most cited source was the International Journal of Physical Distribution & Logistics Management based on the co-citation source analysis, the country with the most documents was China based on the bibliographic coupling country analysis, and the most repeated keywords were e-logistics, e-commerce, logistics, supply chain management and reverse logistics based on the keyword co-occurrence analysis.